Reading reality among university students: A field study on the students of the University of Sharjah - Alblushi, Khadija Ahmed Ibrahim; Khettabi, Ahmed Issa (Al-Adab Journal, 2019)
The aim of the research was to identify the reality of reading among the students of the University of Sharjah, their attitudes towards reading and their motives for that, as it aimed to identify students' reading areas and the obstacles they encounter. The study sample consisted of 120 individual students at the University of Sharjah as a society to study. The questionnaire consisted of four axes: First, Students' attitudes towards reading, Second, Students' motivation towards reading, Third, Reading Areas for Students, Fourth, students' difficulties with Reading. The questionnaire consisted of 46 statements.The main results of the study were as follows:Most of the positive trends towards reading have been widely approved as compared to negative trends.Motivations towards reading came in a variety of terms where all statments obtained the degree of approval.The reading fields of the students of the University of Sharjah were ranked in descending order as follows:Social and cultural fields.Religious Subjects.The riddles and jokes.With regard to the most important obstacles, the results showed that the ease of reliance on modern media as an alternative to reading came first, in addition to the fact that the requirements of the study occupy all the time of students.